VD_FINDINFO HC / 2014 / 1008 vom 24. Dezember 2014 - VD Tribunal cantonal (2014)
CONVENTION DE NEW YORK, SENTENCE ARBITRALE, ABUS DE DROIT, RECONNAISSANCE DE LA DÉCISION, DÉCISION ÉTRANGÈRE, ORDRE PUBLICEN GÉNÉRAL | 85a al. 1 LP, 85a al. 2 LP, 85a LP